A method for preparing a pot-shaped microgel

By using microfluidic technology and polysaccharide modification to prepare pot-shaped microgels, the limitations of existing open-shaped microgel preparation methods and insufficient matrix adjustment were solved, achieving performance optimization and the preparation of multifunctional microgels.

CN116948219BActive Publication Date: 2026-06-30NORTHEASTERN UNIV CHINA
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202311008785.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-08-11
Publication Date
2026-06-30
Estimated Expiration
2043-08-11

AI Technical Summary

Technical Problem

In the existing technology, there are limited methods for preparing open-ended microgels, and the microgel matrix based on the principle of aqueous two-phase separation has insufficient adjustment ability, making it difficult to optimize its performance by adjusting the microgel matrix.

Method used

Water-in-oil microdroplets were prepared using a microfluidic device, and the oil phase was frozen at low temperature and solidified by UV irradiation. Polysaccharides were added to modify the microgels, thus preparing bowl-shaped microgels.

Benefits of technology

Unique bowl-shaped microgels with consistent matrix composition were prepared. The polysaccharides endowed the microgels with anti-inflammatory and anti-tumor properties, expanding the application range of microgels.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116948219B_ABST
    Figure CN116948219B_ABST
Patent Text Reader

Abstract

A method for preparing a bowl-shaped microgel belongs to the field of microgel technology. The specific steps of the preparation method are as follows: 1. Solution preparation: Weigh cetyl polyethylene glycol / polypropylene glycol-10 / 1 dimethylsiloxane (EM 90) and hexadecane to prepare a hexadecane solution containing EM 90; weigh PEGDA, LAP, and polysaccharides to prepare an aqueous solution containing PEGDA, LAP, and polysaccharides; 2. Microdroplet preparation; 3. Microgel preparation; 4. Microgel washing. The oil and surfactant used in this invention are inexpensive and readily available, and the preparation method is simple, avoiding the changes in the microgel matrix caused by the osmotic pressure of the aqueous two-phase phase during the phase separation process in microgels based on the phase separation principle. By incorporating polysaccharides to adjust the composition and structure of the microgel prepolymer solution, bowl-shaped microgels with different matrices can be obtained. The microgels prepared by this invention are expected to be used for disease diagnosis and treatment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of microgel technology, specifically relating to a method for preparing a bowl-shaped microgel. Background Technology

[0002] Hydrogels are highly hydrophilic, three-dimensional network polymers that swell in water but remain insoluble. Their high biocompatibility and similarity to the extracellular matrix have led to their widespread application in tissue engineering and regenerative medicine. Microgels, on the other hand, are hydrogels at the micrometer scale; their size and morphology largely determine their application characteristics and scenarios. Due to their small size, high biocompatibility, and porous structure, microgels are frequently used for drug delivery, cell culture, and the construction of biomimetic materials.

[0003] Many methods for preparing microgels have been explored, such as microemulsion and reverse microemulsion methods, precipitation polymerization, non-wetting template particle replication (PRINT) technology, and droplet microfluidics. Among these, microemulsion, reverse microemulsion, and precipitation polymerization methods struggle to produce microgels with uniform size. Droplet microfluidics, utilizing microfluidic chips, introduces oil and water phases. The oil phase shears the water phase into uniformly sized droplets, thus yielding microgels with uniform and controllable size. Microgels prepared using droplet microfluidics first require the formation of water-in-oil droplets. Light or other stimuli induce polymerization within the water droplets, forming the microgel. Due to surface tension, the water-in-oil droplets are spherical, resulting in a spherical microgel after solidification. Modification of spherical microgels typically involves internal gel matrix or surface modification, making unilateral modification difficult and limiting the application range of microgels.

[0004] Open-cell microgels possess an open cavity structure, and the morphological characteristics of their inner and outer walls further expand their functionality, facilitating the development of multiple applications. Chinese Patent Publication No. CN 102585252A discloses a method for synthesizing non-spherical polymer microparticles. This invention uses an inner, middle, and outer three-phase system to prepare O / W / O microdroplets and prepares open-cell microgels based on three-channel phase separation. During operation, the device can adjust the flow rate ratio of the inner and middle phases to prepare hydrogel microparticles with similar morphologies. However, this device can only synthesize hydrogels based on polyethylene glycol diacrylate (PEGDA) or by incorporating nanoparticles into the substrate. Chinese Patent Publication No. CN 112844259A discloses a method for preparing dual-liquid-core hydrogel microcapsules based on a two-phase aqueous system. This invention is based on the phase separation construction of a polyethylene glycol-dextran aqueous two-phase system, and forms dual-liquid-core hydrogel microcapsules with adjustable size, uniform size, and controllable morphology by adjusting the concentration and flow rate of the system components. The inventions described above all rely on the phase separation phenomenon of PEGDA and dextran, and their microgel matrices are all made of a single PEGDA (polyethylene glycol diacrylate), making it difficult to adjust the microgel matrix. Furthermore, the molecular weight and concentration of PEGDA and dextran are critical during the synthesis process; otherwise, phase separation cannot be achieved.

[0005] Currently, the preparation methods for open-cell microgels are limited, relying on phase separation of the aqueous two-phase system within the droplet. The matrix of open-cell microgels is formed solely from the polymerization of polyethylene glycol diacrylate (PEGDA), resulting in a single matrix and limiting the performance of the microgels to adjusting the matrix concentration. Optimizing the mechanical strength of microgels by designing and adjusting their composition is a fundamental approach. However, microgels prepared based on the aqueous two-phase separation principle lack the ability to adjust and optimize the microgel matrix. A simple, tunable matrix preparation method for open-cell microgels is currently lacking. Summary of the Invention

[0006] In view of the shortcomings of the prior art, the purpose of this invention is to provide a method for preparing bowl-shaped microgels, in which polysaccharides are added to modify the microgels during the preparation process.

[0007] To achieve the above objectives, the present invention uses a microfluidic device to prepare and collect water-in-oil microdroplets, then cools the collected portion to freeze the oil phase, and irradiates the microdroplets with an ultraviolet lamp to solidify them into microgels.

[0008] The microfluidic chip construction process used in this invention is as follows: First, the chip is drawn, and then a mask is made according to the drawn pattern. A 3-inch silicon wafer is taken, and SU-8 2050 photoresist is spin-coated on its surface at 500 rpm for 10 seconds and 2000 rpm for 30 seconds. Then, it is placed on a baking stage to dry at 65°C for 3 minutes, followed by 95°C for 9 minutes. After baking, the mask is placed on top of the silicon wafer and exposed under a photolithography machine for 10 seconds. After photolithography, the silicon wafer is removed and placed on a baking stage, baked at 65°C for 2 minutes, followed by 95°C for 7 minutes. Then, it is developed with PGMEA developer to obtain a positive film. PDMS is then poured onto the positive film, heated at 80°C for 30 minutes, and then demolded. The detached PDMS is punched, treated with oxygen plasma for 13 seconds, and then bonded to a glass slide to obtain a microdroplet microfluidic chip.

[0009] This invention provides a method for preparing bowl-shaped microgels, the process flow of which is as follows: Figure 1 As shown, the specific steps are as follows:

[0010] 1. Solution preparation: Weigh cetyl polyethylene glycol / polypropylene glycol-10 / 1 dimethylsiloxane (EM 90) and hexadecane to prepare a hexadecane solution containing EM 90; weigh polyethylene glycol diacrylate (PEGDA), lithium phenyl (2,4,6-trimethylbenzoyl)phosphinic acid (LAP) and polysaccharide to prepare an aqueous solution containing PEGDA, LAP and polysaccharide, wherein the polysaccharide is selected from any one of sodium alginate (SA), sodium hyaluronate (HA) and sodium carboxymethyl cellulose (CMC-Na).

[0011] The mass fraction of EM 90 in the hexadecane solution is 2-8%.

[0012] The PEGDA has an average molecular weight of 700, the SA has a viscosity of 15-60 mPa·s, the HA has a molecular weight of 8000-15000 Da, and the CMC-Na has a viscosity of 600-3000 mPa·s.

[0013] When the polysaccharide is SA, the mass ratio of PEGDA, LAP and SA is (10-60):(0.1-1):(2-20); wherein the mass fraction of PEGDA is 5-30%, the mass fraction of LAP is 0.05-0.5%, and the mass fraction of SA is 1-10%.

[0014] When HA is selected as the polysaccharide, the mass ratio of PEGDA, LAP and HA is (10-60):(0.1-1):(2-40); wherein the mass fraction of PEGDA is 5-30%, the mass fraction of LAP is 0.05-0.5%, and the mass fraction of HA is 1-20%.

[0015] When CMC-Na is selected as the polysaccharide, the mass ratio of PEGDA, LAP and CMC-Na is (10-60):(0.1-1):(0.4-1), wherein the mass fraction of PEGDA is 5-30%, the mass fraction of LAP is 0.05-0.5%, and the mass fraction of CMC-Na is 0.2-0.5%.

[0016] 2. Preparation of microdroplets: Hexadecane containing EM 90 was injected as the oil phase. Figure 2 The microfluidic chip with the structure shown is injected with an aqueous solution containing PEGDA, LAP, and polysaccharides into its external phase channel. Figure 2 Microfluidic chips have internal phase channels, where microdroplets are collected within the collection channels;

[0017] The injection rate of the outer phase channel is 10-50 μL / min, and the injection rate of the inner phase channel is 0.5-2 μL / min.

[0018] 3. Preparation of microgels: The obtained microdroplets were collected on a glass slide, and after standing, the slide was placed in a low temperature environment. After the oil phase on the slide froze, the sample was irradiated with a light source, and the microdroplets solidified to obtain a bowl-shaped microgel.

[0019] The settling time is 3-10 minutes; the ambient temperature is 0-8℃; the light source is an ultraviolet lamp with a wavelength of 365-405nm;

[0020] 4. Washing of microgels: The solidified microgels were washed with isopropanol and then with anhydrous ethanol to remove hexadecane and EM 90, thus obtaining the prepared microgels.

[0021] The microgel was washed with isopropanol 3-5 times and with anhydrous ethanol 3-5 times.

[0022] The spherical microgels prepared in this invention have an outer cavity diameter of 50-300 μm and an inner cavity diameter of 20-280 μm.

[0023] The microgels prepared in this invention have an upward-facing opening, a round and flat shape, a flat bottom, and a slightly small opening, resembling a bowl. Because the bottom of the microgel is relatively thick and flat, the opening faces upward when submerged in solution. The microgels prepared in this invention have obvious ripples within the opening cavity, which may facilitate cell adhesion within the microgel opening cavity. The bowl-shaped microgels are formed by photopolymerization of water-in-oil droplets after the oil phase has frozen in a low-temperature environment. The preparation method is simple, and the oil and surfactants used are inexpensive and readily available. Since the water-in-oil droplets do not undergo a two-phase phase separation process before photopolymerization, the matrix of the microgel is completely consistent with the composition of the prepolymer solution, avoiding the changes in the microgel matrix caused by the osmotic pressure of the two-phase aqueous phase during phase separation, which is a characteristic of microgels based on the principle of phase separation. By incorporating polysaccharides to adjust the composition and structure of the microgel prepolymer solution, bowl-shaped microgels with different matrices can be obtained. Since polysaccharides have anti-inflammatory, anti-tumor, and immunomodulatory effects, the microgels prepared in this invention hold promise for the diagnosis and treatment of diseases. Attached Figure Description

[0024] Figure 1 Flowchart of the preparation process of jar-shaped microgels;

[0025] Figure 2 A schematic diagram of the microfluidic channel for fabricating microdroplets according to the present invention;

[0026] Figure 3 Scanning electron microscope image of PEDA slurry microgels containing 1% SA;

[0027] Figure 4 Scanning electron microscope image of PEDA slurry microgels containing 2% SA;

[0028] Figure 5 Scanning electron microscope image of PEGDA slurry microgels containing 5% SA;

[0029] Figure 6 Scanning electron microscope image of PEGDA slurry microgels containing 1% HA;

[0030] Figure 7 Scanning electron microscope image of PEGDA slurry microgels containing 5% HA;

[0031] Figure 8 Scanning electron microscope image of PEGDA pot-shaped microgels containing 0.2% CMC-Na;

[0032] Figure 9 Scanning electron microscope image of PEGDA pot-shaped microgels containing 0.5% CMC-Na;

[0033] Figure 10 Scanning electron microscope image of undoped PEGDA slurry microgels. Detailed Implementation

[0034] In this embodiment of the invention, the polyethylene glycol diacrylate (PEGDA) used was provided by Shanghai Maclean Biotechnology Co., Ltd.; lithium phenyl (2,4,6-trimethylbenzoyl)phosphine (LAP) was provided by Shanghai Bid Pharmaceutical Technology Co., Ltd.; sodium alginate (SA) was provided by Shanghai Maclean Biotechnology Co., Ltd.; sodium carboxymethyl cellulose (CMC-Na) was purchased from Sinopharm Chemical Reagent Co., Ltd.; sodium hyaluronate (HA) was provided by Shanghai Maclean Biotechnology Co., Ltd.; EM 90 was provided by Degussa Chemicals (Shanghai) Co., Ltd.; and hexadecane was provided by Shanghai Maclean Biotechnology Co., Ltd.

[0035] In this embodiment of the invention, the microcontroller chip construction process is as follows: First, draw as shown... Figure 2 The chip shown is then used to fabricate a mask based on the drawn pattern. A 3-inch silicon wafer is spin-coated with SU-8 2050 photoresist at 500 rpm for 10 seconds and then at 2000 rpm for 30 seconds. It is then placed on a baking stage to dry at 65°C for 3 minutes, followed by 95°C for 9 minutes. After baking, the mask is placed on top of the silicon wafer and exposed to light for 10 seconds using a photolithography machine. After photolithography, the silicon wafer is removed and placed on the baking stage, where it is baked at 65°C for 2 minutes, followed by 95°C for 7 minutes. It is then developed using PGMEA developer to obtain a positive film. PDMS is then poured onto the positive film, heated at 80°C for 30 minutes, and then demolded. The detached PDMS is perforated, treated with oxygen plasma for 13 seconds, and then bonded to a glass slide to obtain a microfluidic chip for fabricating microdroplets.

[0036] In this embodiment of the invention, the injection flow rate of the microfluidic chip in the outer phase channel is 10 μL / min, and the injection flow rate in the inner phase channel is 1 μL / min.

[0037] Example 1

[0038] 1. Solution preparation: Weigh 0.4g EM 90, add 9.6g hexadecane and mix thoroughly to prepare the oil phase solution; weigh 5mg LAP, 10mg SA, and 0.14g PEGDA, add 845μL deionized water and mix thoroughly to prepare the aqueous phase solution; wherein, the mass fraction of PEGDA is 14%, the mass fraction of LAP is 0.5%, and the mass fraction of SA is 1%.

[0039] 2. Preparation of microdroplets: The aqueous solution prepared above was introduced into the inner phase channel of the chip at a flow rate of 1 μL / min. After the aqueous solution filled the inner phase channel, the oil solution prepared above was introduced into the outer phase channel of the chip at a flow rate of 10 μL / min. When both the aqueous and oil phases flowed naturally, microdroplets could be observed in the outlet channel.

[0040] 3. Collection of microdroplets: Allow the microdroplets from the outlet to fall naturally onto the glass slide and let stand for 5 minutes. Alternatively, collect the microdroplets in a centrifuge tube and remove them with a pipette when needed.

[0041] 4. Formation of microgels: A glass slide with microdroplets was placed horizontally in an environment of 0-8℃. When the oil phase on the slide was observed to turn into a white opaque state, the microdroplets were solidified by in-situ irradiation with a 395nm light source to obtain a bowl-shaped microgel.

[0042] 5. Washing of microgels: The solidified microgels were washed three times with isopropanol, and then three times with anhydrous ethanol to remove hexadecane and EM 90, yielding the prepared bowl-shaped microgels. Scanning electron microscopy images are shown below. Figure 3 As shown, the outer cavity diameter is 82 μm and the inner cavity diameter is 52 μm.

[0043] Example 2

[0044] 1. Solution preparation: Weigh 0.4g EM 90, add 9.6g hexadecane and mix thoroughly to form the oil phase solution; weigh 5mg LAP, 20mg SA, and 0.14g PEGDA, add 835μL deionized water and mix thoroughly to form the aqueous phase solution; wherein, the mass fraction of PEGDA is 14%, the mass fraction of LAP is 0.5%, and the mass fraction of SA is 2%.

[0045] 2. Preparation of microdroplets: The aqueous solution prepared above was introduced into the inner phase channel of the chip at a flow rate of 1 μL / min. After the aqueous solution filled the inner phase channel, the oil solution prepared above was introduced into the outer phase channel of the chip at a flow rate of 10 μL / min. When both the aqueous and oil phases flowed naturally, microdroplets could be observed in the outlet channel.

[0046] 3. Collection of microdroplets: Allow the microdroplets from the outlet to fall naturally onto the glass slide and let stand for 5 minutes. Alternatively, collect the microdroplets in a centrifuge tube and remove them with a pipette when needed.

[0047] 4. Formation of microgels: A glass slide with microdroplets was placed horizontally in an environment of 0-8℃. When the oil phase on the slide was observed to turn into a white opaque state, the microdroplets were solidified by in-situ irradiation with a 395nm light source to obtain a bowl-shaped microgel.

[0048] 5. Washing of microgels: The solidified microgels were washed three times with isopropanol, and then three times with anhydrous ethanol to remove hexadecane and EM 90, yielding the prepared bowl-shaped microgels. Scanning electron microscopy images are shown below. Figure 4 As shown, the outer cavity diameter is 80μm and the inner cavity diameter is 53μm.

[0049] Example 3

[0050] 1. Solution preparation: Weigh 0.4g EM 90, add 9.6g hexadecane and mix thoroughly to prepare the oil phase solution; weigh 5mg LAP, 50mg SA, and 0.14g PEGDA, add 805μL deionized water and mix thoroughly to prepare the aqueous phase solution; wherein the mass fraction of PEGDA is 14%, the mass fraction of LAP is 0.5%, and the mass fraction of SA is 5%.

[0051] 2. Preparation of microdroplets: The aqueous solution prepared above was introduced into the inner phase channel of the chip at a flow rate of 1 μL / min. After the aqueous solution filled the inner phase channel, the oil solution prepared above was introduced into the outer phase channel of the chip at a flow rate of 10 μL / min. When both the aqueous and oil phases flowed naturally, microdroplets could be observed in the outlet channel.

[0052] 3. Collection of microdroplets: Allow the microdroplets from the outlet to fall naturally onto the glass slide and let stand for 5 minutes. Alternatively, collect the microdroplets in a centrifuge tube and remove them with a pipette when needed.

[0053] 4. Formation of microgels: A glass slide with microdroplets was placed horizontally in an environment of 0-8℃. When the oil phase on the slide was observed to turn into a white opaque state, the microdroplets were solidified by in-situ irradiation with a 395nm light source to obtain a bowl-shaped microgel.

[0054] 5. Washing of microgels: The solidified microgels were washed three times with isopropanol, and then three times with anhydrous ethanol to remove hexadecane and EM 90, yielding the prepared bowl-shaped microgels. Scanning electron microscopy images are shown below. Figure 5 As shown, the outer cavity diameter is 92 μm and the inner cavity diameter is 44 μm.

[0055] Example 4

[0056] 1. Solution preparation: Weigh 0.4g EM 90, add 9.6g hexadecane and mix thoroughly to prepare the oil phase solution; weigh 5mg LAP, 10mg HA, and 0.14g PEGDA, add 845μL deionized water and mix thoroughly to prepare the aqueous phase solution; wherein, the mass fraction of PEGDA is 14%, the mass fraction of LAP is 0.5%, and the mass fraction of HA is 1%.

[0057] 2. Preparation of microdroplets: The aqueous solution prepared above was introduced into the inner phase channel of the chip at a flow rate of 1 μL / min. After the aqueous solution filled the inner phase channel, the oil solution prepared above was introduced into the outer phase channel of the chip at a flow rate of 10 μL / min. When both the aqueous and oil phases flowed naturally, microdroplets could be observed in the outlet channel.

[0058] 3. Collection of microdroplets: Allow the microdroplets from the outlet to fall naturally onto the glass slide and let stand for 5 minutes. Alternatively, collect the microdroplets in a centrifuge tube and remove them with a pipette when needed.

[0059] 4. Formation of microgels: A glass slide with microdroplets was placed horizontally in an environment of 0-8℃. When the oil phase on the slide was observed to turn into a white opaque state, the microdroplets were solidified by in-situ irradiation with a 395nm light source to obtain a bowl-shaped microgel.

[0060] 5. Washing of microgels: The solidified microgels were washed three times with isopropanol, and then three times with anhydrous ethanol to remove hexadecane and EM 90, yielding the prepared bowl-shaped microgels. Scanning electron microscopy images are shown below. Figure 6 As shown, the outer cavity diameter is 86 μm and the inner cavity diameter is 54 μm.

[0061] Example 5

[0062] 1. Solution preparation: Weigh 0.4g EM 90, add 9.6g hexadecane and mix thoroughly to prepare the oil phase solution; weigh 5mg LAP, 50mg HA, and 0.14g PEGDA, add 805μL deionized water and mix thoroughly to prepare the aqueous phase solution; wherein, the mass fraction of PEGDA is 14%, the mass fraction of LAP is 0.5%, and the mass fraction of HA is 5%.

[0063] 2. Preparation of microdroplets: The aqueous solution prepared above was introduced into the inner phase channel of the chip at a flow rate of 1 μL / min. After the aqueous solution filled the inner phase channel, the oil solution prepared above was introduced into the outer phase channel of the chip at a flow rate of 10 μL / min. When both the aqueous and oil phases flowed naturally, microdroplets could be observed in the outlet channel.

[0064] 3. Collection of microdroplets: Allow the microdroplets from the outlet to fall naturally onto the glass slide and let stand for 5 minutes. Alternatively, collect the microdroplets in a centrifuge tube and remove them with a pipette when needed.

[0065] 4. Formation of microgels: A glass slide with microdroplets was placed horizontally in an environment of 0-8℃. When the oil phase on the slide was observed to turn into a white opaque state, the microdroplets were solidified by in-situ irradiation with a 395nm light source to obtain a bowl-shaped microgel.

[0066] 5. Washing of microgels: The solidified microgels were washed three times with isopropanol, and then three times with anhydrous ethanol to remove hexadecane and EM 90, yielding the prepared bowl-shaped microgels. Scanning electron microscopy images are shown below. Figure 7 As shown, the outer cavity diameter is 85μm and the inner cavity diameter is 59μm.

[0067] Example 6

[0068] 1. Solution preparation: Weigh 0.4g EM 90, add 9.6g hexadecane and mix thoroughly to form the oil phase solution; weigh 5mg LAP, 2mg CMC-Na, and 0.14g PEGDA, add 853μL deionized water and mix thoroughly to form the aqueous phase solution; wherein, the mass fraction of PEGDA is 14%, the mass fraction of LAP is 0.5%, and the mass fraction of CMC-Na is 0.2%.

[0069] 2. Preparation of microdroplets: The aqueous solution prepared above was introduced into the inner phase channel of the chip at a flow rate of 1 μL / min. After the aqueous solution filled the inner phase channel, the oil solution prepared above was introduced into the outer phase channel of the chip at a flow rate of 10 μL / min. When both the aqueous and oil phases flowed naturally, microdroplets could be observed in the outlet channel.

[0070] 3. Collection of microdroplets: Allow the microdroplets from the outlet to fall naturally onto the glass slide and let stand for 5 minutes. Alternatively, collect the microdroplets in a centrifuge tube and remove them with a pipette when needed.

[0071] 4. Formation of microgels: A glass slide with microdroplets was placed horizontally in an environment of 0-8℃. When the oil phase on the slide was observed to turn into a white opaque state, the microdroplets were solidified by in-situ irradiation with a 395nm light source to obtain a bowl-shaped microgel.

[0072] 5. Washing of microgels: The solidified microgels were washed three times with isopropanol, and then three times with anhydrous ethanol to remove hexadecane and EM 90, yielding the prepared bowl-shaped microgels. Scanning electron microscopy images are shown below. Figure 8 As shown, the outer cavity diameter is 82 μm and the inner cavity diameter is 50 μm.

[0073] Example 7

[0074] 1. Solution preparation: Weigh 0.4g EM 90, add 9.6g hexadecane and mix thoroughly to prepare the oil phase solution; weigh 5mg LAP, 5mg CMC-Na, and 0.14g PEGDA, add 850μL deionized water and mix thoroughly to prepare the aqueous phase solution; wherein, the mass fraction of PEGDA is 14%, the mass fraction of LAP is 0.5%, and the mass fraction of CMC-Na is 0.5%.

[0075] 2. Preparation of microdroplets: The aqueous solution prepared above was introduced into the inner phase channel of the chip at a flow rate of 1 μL / min. After the aqueous solution filled the inner phase channel, the oil solution prepared above was introduced into the outer phase channel of the chip at a flow rate of 10 μL / min. When both the aqueous and oil phases flowed naturally, microdroplets could be observed in the outlet channel.

[0076] 3. Collection of microdroplets: Allow the microdroplets from the outlet to fall naturally onto the glass slide and let stand for 5 minutes. Alternatively, collect the microdroplets in a centrifuge tube and remove them with a pipette when needed.

[0077] 4. Formation of microgels: A glass slide with microdroplets was placed horizontally in an environment of 0-8℃. When the oil phase on the slide was observed to turn into a white opaque state, the microdroplets were solidified by in-situ irradiation with a 395nm light source to obtain a bowl-shaped microgel.

[0078] 5. Washing of microgels: The solidified microgels were washed three times with isopropanol, and then three times with anhydrous ethanol to remove hexadecane and EM 90, yielding the prepared bowl-shaped microgels. Scanning electron microscopy images are shown below. Figure 9 As shown, the outer cavity diameter is 83 μm and the inner cavity diameter is 46 μm.

[0079] Comparative Example 1

[0080] 1. Solution preparation: Weigh 0.4g EM 90, add 9.6g hexadecane and mix thoroughly to prepare the oil phase solution; weigh 5mg LAP and 0.14g PEGDA, add 855μL deionized water and mix thoroughly to prepare the aqueous phase solution.

[0081] The mass fraction of PEGDA was 14%, and the mass fraction of LAP was 0.5%.

[0082] 2. Preparation of microdroplets: The aqueous solution prepared above was introduced into the inner phase channel of the chip at a flow rate of 1 μL / min. After the aqueous solution filled the inner phase channel, the oil solution prepared above was introduced into the outer phase channel of the chip at a flow rate of 10 μL / min. When both the aqueous and oil phases flowed naturally, microdroplets could be observed in the outlet channel.

[0083] 3. Collection of microdroplets: Allow the microdroplets from the outlet to fall naturally onto the glass slide and let stand for 5 minutes. Alternatively, collect the microdroplets in a centrifuge tube and remove them with a pipette when needed.

[0084] 4. Formation of microgels: A glass slide with microdroplets was placed horizontally in an environment of 0-8℃. When the oil phase on the slide was observed to turn into a white opaque state, the microdroplets were solidified by in-situ irradiation with a 395nm light source to obtain a bowl-shaped microgel.

[0085] 5. Washing of microgels: The solidified microgels were washed three times with isopropanol, and then three times with anhydrous ethanol to remove hexadecane and EM 90, yielding the prepared bowl-shaped microgels. Scanning electron microscopy images are shown below. Figure 10 As shown, the outer cavity diameter is 117 μm and the inner cavity diameter is 49 μm.

Claims

1. A method for preparing a bowl-shaped microgel, characterized in that, The specific steps are as follows: (1) Solution preparation: Weigh cetyl polyethylene glycol / polypropylene glycol-10 / 1 dimethylsiloxane and hexadecane to prepare a hexadecane solution containing cetyl polyethylene glycol / polypropylene glycol-10 / 1 dimethylsiloxane; weigh polyethylene glycol diacrylate, lithium phenyl (2,4,6-trimethylbenzoyl)phosphinate and polysaccharide to prepare an aqueous solution containing polyethylene glycol diacrylate, lithium phenyl (2,4,6-trimethylbenzoyl)phosphinate and polysaccharide; the polysaccharide is selected from any one of sodium alginate, sodium hyaluronate and sodium carboxymethyl cellulose; When sodium alginate is selected as the polysaccharide, the mass ratio of polyethylene glycol diacrylate, lithium phenyl (2,4,6-trimethylbenzoyl)phosphinic acid oxide, and sodium alginate is (10-60):(0.1-1):(2-20); wherein the mass fraction of polyethylene glycol diacrylate is 5-30%, the mass fraction of lithium phenyl (2,4,6-trimethylbenzoyl)phosphinic acid oxide is 0.05-0.5%, and the mass fraction of sodium alginate is 1-10%. When sodium hyaluronate is selected as the polysaccharide, the mass ratio of polyethylene glycol diacrylate, lithium phenyl(2,4,6-trimethylbenzoyl)phosphinic acid to sodium hyaluronate is (10-60):(0.1-1):(2-40); wherein the mass fraction of polyethylene glycol diacrylate is 5-30%, the mass fraction of lithium phenyl(2,4,6-trimethylbenzoyl)phosphinic acid is 0.05-0.5%, and the mass fraction of sodium hyaluronate is 1-20%. When sodium carboxymethyl cellulose is selected as the polysaccharide, the mass ratio of polyethylene glycol diacrylate, lithium phenyl(2,4,6-trimethylbenzoyl)phosphinic acid, and sodium carboxymethyl cellulose is (10-60):(0.1-1):(0.4-1); wherein the mass fraction of polyethylene glycol diacrylate is 5-30%, the mass fraction of lithium phenyl(2,4,6-trimethylbenzoyl)phosphinic acid is 0.05-0.5%, and the mass fraction of sodium carboxymethyl cellulose is 0.2-0.5%. (2) Preparation of microdroplets: The prepared hexadecane solution containing cetyl polyethylene glycol / polypropylene glycol-10 / 1 dimethylsiloxane was injected as the oil phase into the outer phase channel of the microfluidic chip, and the prepared aqueous solution containing polyethylene glycol diacrylate, lithium phenyl (2,4,6-trimethylbenzoyl)phosphinic acid and polysaccharide was injected into the inner phase channel of the microfluidic chip to obtain microdroplets in the collection channel; (3) Preparation of microgels: The obtained microdroplets were collected on a glass slide and allowed to stand. The slide was then placed in a low temperature environment of 0-8℃. After the oil phase on the slide froze, the sample was irradiated with a light source and the microdroplets solidified to obtain a bowl-shaped microgel. (4) Washing of microgels: The solidified microgels were washed with isopropanol and then with anhydrous ethanol to remove hexadecane and cetyl polyethylene glycol / polypropylene glycol-10 / 1 dimethylsiloxane, thus obtaining the prepared microgels.

2. The method for preparing a bowl-shaped microgel according to claim 1, characterized in that, The mass fraction of cetyl polyethylene glycol / polypropylene glycol-10 / 1 dimethylsiloxane in the hexadecane solution is 2-8%; The polyethylene glycol diacrylate has an average molecular weight of 700, sodium alginate has a viscosity of 15-60 mPa·s, sodium hyaluronate has a molecular weight of 8000-15000 Da, and sodium carboxymethyl cellulose has a viscosity of 600-3000 mPa·s.

3. The method for preparing a bowl-shaped microgel according to claim 1, characterized in that, In step (2), the injection rate of the outer phase channel is 10-50 μL / min, and the injection rate of the inner phase channel is 0.5-2 μL / min.

4. The method for preparing a bowl-shaped microgel according to claim 1, characterized in that, In step (3), the settling time is 3-10 min; the light source is an ultraviolet lamp with a wavelength of 365-405 nm.

5. The method for preparing a bowl-shaped microgel according to claim 1, characterized in that, In step (4), the microgel is washed with isopropanol 3-5 times and with anhydrous ethanol 3-5 times.

6. A bowl-shaped microgel, characterized in that, It is prepared by the preparation method according to any one of claims 1-5.

7. The bowl-shaped microgel according to claim 6, characterized in that, The microgel has an outer cavity diameter of 50-300 μm and an inner cavity diameter of 20-280 μm.

Citation Information

Patent Citations

  • Method for synthesizing nonspherical polymer microparticles

    CN102585252A

  • Preparation method of double-liquid-core hydrogel microcapsule based on double aqueous phases

    CN112844259A

  • Method for preparing micro-nano gel microspheres based on metastable emulsion

    CN112495316A

  • Anti-swelling microgel as well as preparation method and application thereof

    CN116239806A